RELATIONSHIP OF SERVICE QUALITY WITH PATIENT SATISFACTION OF SUKADANA PUSKESMAS EAST LAMPUNG. ESSAY - Ery Baskoro; Adi Kurniawan (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
In the current era of globalization excellent service is a major element in hospitals and health units. Hospitals are required to provide health services that serve optimal service standards. The hospital or puskesmas is declared successful, not only in the completeness of the superior facilities, but also the attitudes and services of human resources are the elements that significantly affect the service produced and perceived by the patient One of the medical services in Sukadana Public Health Center East Lampung, is one of the health centers that handle patients who have severedisease. So that needs to be done quickly and precisely. The health unit ofthe puskesmas provides 24-hour service with midwife and paramedic personnel responsible for all emergency services. The purpose of this research his to know empathy relationship with patients at is factionat East Lampung Sukadana Health Center. The type of this research his descriptive research. File collection technique suse primary file and secondary file. The analysis to ol used is a simple regression model with T test. Conclusion, Empathy has no significant effect. Or an employee'scircumstances to fur ther improveits performance in serving Patient Sukadana Puskesmas East Lampung.